2019
DOI: 10.3390/ijerph16193698
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Based Medical Device for Treatment of Alveolar Osteitis—Clinical Study

Abstract: Alveolar Osteitis (AO) is a complication following the extraction of a tooth. AO manifests through localized pain in, and around, the extraction site, where the post-operative blood clot has been disintegrated. The aim of this single cohort study was to evaluate the outcome of a treatment of AO, using a pharmacological device composed of hyaluronic acid and octenidine dihydrochloride. The tested device is a sponge-like material, composed solely of a fully dissoluble medicaments (hyaluronic acid, calcium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 28 publications
0
21
1
6
Order By: Relevance
“…Type I collagen was used as a migration influence coating, adhesion, proliferation and differentiation of cells on titanium implants improving early osteogenesis but without formation of bone far from the surface of the same. The positive influence coating of titanium implants through the use of biomolecules was also confirmed in small pig’s models; in the experimental study, the authors found a greater correlation between implant and bone density increase [ 64 , 65 , 66 ].…”
Section: Studies On Surface Modifications Of Dental Implants Using Hamentioning
confidence: 85%
“…Type I collagen was used as a migration influence coating, adhesion, proliferation and differentiation of cells on titanium implants improving early osteogenesis but without formation of bone far from the surface of the same. The positive influence coating of titanium implants through the use of biomolecules was also confirmed in small pig’s models; in the experimental study, the authors found a greater correlation between implant and bone density increase [ 64 , 65 , 66 ].…”
Section: Studies On Surface Modifications Of Dental Implants Using Hamentioning
confidence: 85%
“…KH je glykosaminoglykan, který má pro své protizánětlivé, hydratační, regenerační, osteokonduktivní a biokompatibilní vlastnosti potenciál využití i ve stomatologii [40,41]. Díky variabilním možnostem jeho technologického zpracování je k dispozici ve formě spongiózní, tuhé, gelu či prášku, a dovoluje tak zvolit ideální provedení podle místa aplikace [42].…”
Section: Diskuse a Závěrunclassified
“…KH je tak široce využitelným materiálem pro celou řadu indikací. Na našem pracovišti jsme úspěšně otestovali aplikaci spongiózního materiálu vzniklého lyofilizací roztoku KH s oktenidin dihydrochloridem pro léčbu alveolární ostitis [40]. Při autologní transplantaci fibroblastů kolonizujících nosič z KH byl tento materiál použit jako štěp pro krytí gingiválních recesů [43,44].…”
Section: Diskuse a Závěrunclassified
“…A new remedy based on hyaluronic acid (HA) and octenidine (OCT) is currently in Phase II of a clinical trial. It was developed for the treatment and prevention of AO [15].…”
Section: Introductionmentioning
confidence: 99%